2014
DOI: 10.1111/jbg.12115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of calf and heifer survival in Iranian Holstein cattle using linear and threshold models

Abstract: Calf and heifer survival are important traits in dairy cattle affecting profitability. This study was carried out to estimate genetic parameters of survival traits in female calves at different age periods, until nearly the first calving. Records of 49,583 female calves born during 1998 and 2009 were considered in five age periods as days 1-30, 31-180, 181-365, 366-760 and full period (day 1-760). Genetic components were estimated based on linear and threshold sire models and linear animal models. The models i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
4
1
Order By: Relevance
“…Low to moderate genetic correlations were observed among Sur1, Sur2, and Sur3, which agrees with the literature (Forutan et al, 2015;Pathak et al, 2018). There are differences on the replacement survival trait definitions across studies, and, as expected, higher genetic correlations are observed between survival indica-tors based on similar or adjacent life stages (Harbers et al, 2002;Hansen et al, 2003;Fuerst-Waltl and Sørensen, 2010;Pathak et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Low to moderate genetic correlations were observed among Sur1, Sur2, and Sur3, which agrees with the literature (Forutan et al, 2015;Pathak et al, 2018). There are differences on the replacement survival trait definitions across studies, and, as expected, higher genetic correlations are observed between survival indica-tors based on similar or adjacent life stages (Harbers et al, 2002;Hansen et al, 2003;Fuerst-Waltl and Sørensen, 2010;Pathak et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Generally, replacement survivability has been defined as binary traits corresponding to the survival during various life stages from birth to first calving. In Iranian (Forutan et al, 2015), UK and US (Pritchard et al, 2013), Danish (Fuerst-Waltl and Sørensen, 2010), and Dutch (Harbers et al, 2002) Holstein cattle; Austrian (Fuerst-Waltl and Fuerst, 2012) and US (Erf et al, 1990) Brown Swiss; Danish Jersey (Norberg et al, 2013); and Spanish local beef cattle (Asturian Valley breed; Goyache et al, 2003) populations, the heritability of replacement survival ranged from 0.01 to 0.14. In US Holstein (Gonzalez-Peña et al, 2019) and Jersey (Gonzalez-Peña et al, 2020) cattle, genomic evaluation on replacement survivability defined as a binary trait between 2 and 365 d of age has been performed with a reliability of 47.3 to 50.5%.…”
Section: Genetic Parameters For Dairy Calf and Replacement Heifer Wel...mentioning
confidence: 99%
“…However, the heritability obtained in ABT model (Table 4) can be considered overstated and incorrect when compared to the values estimated through the other analytical models. In the studies of Van Tassel et al (1998), Cole et al (2007), and Forutan, Mahyari, and Sargolzaei (2015) which also involved threshold models, the frequency of each categorical class was higher than in the present study (4.6% of mortality versus 95.4% of survival). Thus, the overestimation of the variance components by using the ABT model can be due to the low frequency of some SW phenotypes.…”
Section:    contrasting
confidence: 74%
“…Variance components and genetic parameters for categorical traits can be estimated in a one-trait or two-trait analyse under the assumption of linear (Forutan, Mahyari, & Sargolzaei, 2015) or threshold distribution of phenotypes (Faria et al, 2010;Forutan, Mahyari, & Sargolzaei, 2015), by using sire or animal models (Forutan, Mahyari, & Sargolzaei, 2015); and by adopting restricted maximum likelihood (REML, Queiroz et al, 2011), Bayesian (Santana Jr. et al, 2013) or generalized linear mixed model approaches (GLMM, Forutan, Mahyari, & Sargolzaei, 2015) as estimation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The methodologies vary according to the number of evaluated traits, the nature of the phenotypic data distribution, the genetic structure adopted and the estimation method of the variance components. For example, by the assumption of linear (Gordo et al, 2012;Forutan, Mahyari, & Sargolzaei, 2015) or threshold distribution of phenotypes (Faria et al, 2009;Boligon et al, 2012;Forutan, Mahyari, & Sargolzaei, 2015), by using sire or animal models (Forutan, Mahyari, & Sargolzaei, 2015); and by adopting restricted maximum likelihood (Bouquet et al, 2010;Queiroz et al, 2011), Bayesian (Boligon et al, 2012;Santana Jr. et al, 2013) or generalized linear mixed model approaches (Forutan, Mahyari, & Sargolzaei, 2015) as estimation methods. These methodologies can be applied in a combined way.…”
Section: Introductionmentioning
confidence: 99%